Peran Mahkamah Konstitusi dalam Menjamin Kedaulatan Hukum di Indonesia - Anggreni, Devi; Fuadi, Ahmad; Fitriyani, Fitriyani; Al-Kautsar, Muhammad Ibnu (Hutanasyah : Jurnal Hukum Tata Negara, 2024)
The Constitutional Court (CC) plays a crucial role in safeguarding the rule of law in Indonesia by ensuring that all laws and governmental policies adhere to the country's constitution. This research explores how the CC functions as an independent guardian of the constitution, balancing power among branches of government, and protecting citizens' rights from potential abuses of power. Through a qualitative approach utilizing literature review, this study analyzes the establishment history, organizational structure, and authority of the CC to conduct judicial reviews on laws deemed unconstitutional.Findings indicate that the CC has played a pivotal role in ensuring legal consistency and constitutional justice in Indonesia. CC decisions, whether through law reviews or constitutional interpretations, have provided the necessary legal certainty for political and economic stability in the country. However, the research also identifies several challenges facing the CC, including political pressures, resource limitations, and the need to enhance compliance with CC decisions among relevant stakeholders. In conclusion, the Indonesian CC holds a vital role in upholding the rule of law by ensuring that the constitution serves as a respected foundation for all within the nation. To maintain relevance amidst evolving social and political dynamics, the CC must continue to enhance its independence as a fair and impartial judicial institution. This study contributes significantly to understanding how the CC contributes to building a democratic and just legal system in Indonesia.